Visualization of the Character's Appearance in Fiction - Natalia A. Drovaleva (Studia Litterarum)
Numerous papers have been written on the topic of portrait creation in literature, viewing it both directly and indirectly, however it remains a topical issue up to this day. It is evidently necessary to systemize the data, gathered by numerous literary research on the portrait characteristics. In this regard, it appears productive to point out the theoretical and methodological particularities of researching a character’s appearance in literature, the existing research notions on the portrait in fiction literature and visual arts and the notable peculiarities of creating a character’s appearance, using examples from prose works of the Silver Age specifically. This period saw the rise of tendencies that consisted of moving away from an actual depiction of reality and the obligatory establishment of connections between external and internal features of the character. By examining various scholarly theories, the author points out that as a result of close attention to the artistic portrait, typical for the end of the 20th century, many works of that period that studied the particularities of characters’ appearance mirrored the notions about graphic and artistic portraits. Traditionally the portrait was researched in connection with the general history of art, and its depicting and artistic function was being actualized. However, it is not the primary function of the portrait, even if it could prove to be productive to research it in the case of painting writers or writing painters (for example M.A. Voloshin and K.A. Korovin). The author draws a specific conclusion that it would be impractical to distinguish a portrait as a closed integrity, and that the phrase “appearance visualization” seems to be the most fitting for describing the portrait features in works of fiction, as opposed to the literary portraits in biographical literature that portray and recreate the image of an existing person.